Enhanced proteomic profiling of human plasma‐derived extracellular vesicles through charge‐based fractionation to advance biomarker discovery potential - Xianyi Su; Getúlio Pereira de Oliveira Júnior; Anne‐Lise Marie; Michal Gregus; Amanda Figueroa‐Navedo; Ionita C. Ghiran; Alexander R. Ivanov (Journal of Extracellular Vesicles)
Abstract The study introduces a charge‐based fractionation method for fractionating plasma‐derived extracellular vesicles (EVs) into sub‐populations aimed at the improved purification from free plasma proteins to enhance the diagnostic potential of EV sub‐populations for specific pathophysiological states. Here, we present a novel approach for EV fractionation that leverages EVs’ inherent surface charges, differentiating them from other plasma components and, thus, reducing the sample complexity and increasing the purity of EVs. The developed method was optimized and thoroughly evaluated using proteomic analysis, transmission electron microscopy, nanoparticle tracking, and western blotting of isolated EVs from healthy donors. Subsequently, we pilot‐tested the developed technique for its applicability to real‐world specimens using a small set of clinical prostate cancer samples and matched controls. The presented technique demonstrates the effective isolation and fractionation of EV sub‐populations based on their surface charge, which may potentially help enhance EV‐based diagnostics, biomarker discovery, and basic biology research. The method is designed to be straightforward, scalable, easy‐to‐use, and it does not require specialized skills or equipment.